Inferior gluteal artery detection at the greater sciatic notch with a computer-assisted navigation system during pelvic and sacral tumor resection. Issue 1 (1st January 2016) - Akiyama, Toru; Kanda, Shotaro; Maeda, Akinori; Saita, Kazuo
Abstract: Background: During pelvic and sacral tumor resection, important vessels, such as the inferior gluteal artery underneath the sciatic notch, are easily injured because of their invisibility. We employed a computer-assisted navigation system to preserve the inferior gluteal artery at the sciatic notch with visualization of the inferior gluteal artery at the sciatic notch, thus maintaining blood flow to the gluteus maximus. Methods: We present the results of seven patients (five men and two women) with a mean age of 64.8 years (58.4–78.8) in whom computer-assisted navigation surgery had been carried out for pelvic and sacral tumor resections. Results: Postoperative enhanced computed tomography (CT) confirmed the preservation of the inferior gluteal artery in all cases. At a mean follow-up of 21.3 months (3–39), the total postoperative complication rate was 25% ( n  = 2), including hematoma ( n  = 1) and wound necrosis ( n  = 1). There were no cases of deep infection. Conclusion: This new application of computer-assisted navigation to pelvic and sacral tumor resection can contribute to reducing postoperative complications related to insufficient flap perfusion.